Registration Data Discrepancy E-Court with Implementation Trial E-Litigation at the Pemalang Religious Court - Miladia Qiya Akhmas Akhmas; Dian Latifiani Latifiani (Universitas Negeri Semarang, 2026)
Digital transformation in the judiciary represents a strategic effort to enhance efficiency, transparency, and access to justice through the implementation of electronic court systems. At the institutional level, E-Court functions as an electronic case administration platform, while E-Litigation is designed to facilitate electronic hearings as an integrated continuation of the registration process. However, empirical data from the Religious Court of Pemalang during the period 2022–2024 indicates a significant and consistent discrepancy between the number of cases registered through E-Court and those processed through E-Litigation. This study aims to analyze the factors causing the discrepancy and to examine the strategies undertaken by the Religious Court of Pemalang in addressing the low utilization of E-Litigation. The research employs a socio-legal approach through field data collection based on in-depth interviews with court officials and practicing advocates. The findings reveal that the discrepancy is influenced by multiple factors, including low digital literacy among litigants, preference for face-to-face hearings, conventional legal culture, strategic considerations of advocates, the consent-based nature of electronic hearings, and institutional limitations. In response, the court has implemented strategies such as socialization programs, technical assistance services, legal aid support, capacity building for court personnel, system integration, and internal monitoring. Nevertheless, the increase in E-Court usage has not been proportionally followed by the adoption of E-Litigation. The study concludes that judicial digitalization requires not only technological infrastructure but also cultural adaptation, institutional strengthening, and enhanced public digital capacity to achieve effective integration between electronic administration and electronic hearings.